Techno-economic assessment of a photovoltaic module integrated with a two-layer phase change material unit. (July 2022) - Narjabadifam, Nima; Salemi, Sina; Adib, Mohammad; Bozorgmehri, Shahriar
Abstract: The excessive temperature rise adversely affects the conversion efficiency and lifespan of photovoltaic cells. A novel cooling system that entails a two-layer phase change material (PCM) unit and a water storage is employed to regulate the temperature of the photovoltaic (PV) module. The techno-economic characteristics of the proposed system are investigated in detail. A computational fluid dynamics (CFD) method is used to evaluate the performance of the integrated (photovoltaic-thermal-phase change material) PVT-PCM system in four different climate conditions. A comprehensive parametric study on design conditions is also carried out to choose the geometric variables and PCM materials that generate the highest improvement in the electrical energy production. The results show when the proper design and climate conditions are met, the proposed cooling system is able to increase the annual electrical energy production of the PV module up to 3.11% compared to the PV module without a PCM cooling unit and to heat the water to the temperature of 48°C. Based on the economic analysis of the proposed PVT-PCM system, it was found that implementing the cooling unit is not economically justifiable due to the high initial price of PCMs. Highlights: The performance a two-layer PCM unit coupled with a water storage is studied for different climatic conditions. Using the low-melting-point PCM for both layers results in the highest improvement. The hot and humid climate condition has the highest potential for implementing the proposed cooling system. Due to the high price of PCM, the proposed system is not economically justifiable.